Concerning influences of micro/nano plastics on female reproductive health: focusing on cellular and molecular pathways from animal models to human studies - Hasti Balali; Ali Morabbi; Mohammad Karimian (BMC, 2024)
Abstract The female reproductive system can face serious disorders and show reproductive abnormalities under the influence of environmental pollutants. Microplastics (MPs) and nanoplastics (NPs) as emerging pollutants, by affecting different components of this system, may make female fertility a serious challenge. Animal studies have demonstrated that exposure to these substances weakens the function of ovaries and causes a decrease in ovarian reserve capacity. Also, continuous exposure to micro/nano plastics (MNPs) leads to increased levels of reactive oxygen species, induction of oxidative stress, inflammatory responses, apoptosis of granulosa cells, and reduction of the number of ovarian follicles. Furthermore, by interfering with the hypothalamic-pituitary-ovarian axis, these particles disturb the normal levels of ovarian androgens and endocrine balance and delay the growth of gonads. Exposure to MNPs can accelerate carcinogenesis in the female reproductive system in humans and animal models. Animal studies have determined that these particles can accumulate in the placenta, causing metabolic changes, disrupting the development of the fetus, and endangering the health of future generations. In humans, the presence of micro/nanoplastics in placenta tissue, infant feces, and breast milk has been reported. These particles can directly affect the health of the mother and fetus, increasing the risk of premature birth and other pregnancy complications. This review aims to outline the hazardous effects of micro/nano plastics on female reproductive health and fetal growth and discuss the results of animal experiments and human research focusing on cellular and molecular pathways.